Thin films with disordered nanohole patterns for solar radiation absorbers. (June 2015) - Fang, Xing; Lou, Minhan; Bao, Hua; Zhao, C.Y.
Abstract: The radiation absorption in thin films with three disordered nanohole patterns, i.e., random position, non-uniform radius, and amorphous pattern, are numerically investigated by finite-difference time-domain (FDTD) simulations. Disorder can alter the absorption spectra and has an impact on the broadband absorption performance. Compared to random position and non-uniform radius nanoholes, amorphous pattern can induce a much better integrated absorption. The power density spectra indicate that amorphous pattern nanoholes reduce the symmetry and provide more resonance modes that are desired for the broadband absorption. The application condition for amorphous pattern nanoholes shows that they are much more appropriate in absorption enhancement for weak absorption materials. Amorphous silicon thin films with disordered nanohole patterns are applied in solar radiation absorbers. Four configurations of thin films with different nanohole patterns show that interference between layers in absorbers will change the absorption performance. Therefore, it is necessary to optimize the whole radiation absorbers although single thin film with amorphous pattern nanohole has reached optimal absorption. Highlights: Absorption characteristics of three disordered nanohole patterns are investigated. Amorphous pattern nanoholes have better integrated absorption. Application conditions of amorphous pattern nanoholes are proposed. Absorption in radiation absorbers with disordered nanohole pattern is studied. Amorphous pattern nanoholes can improve the absorption in neighbor layers.